2009
DOI: 10.1177/1089253209347895
|View full text |Cite
|
Sign up to set email alerts
|

Update on Safety Equipment for Extracorporeal Life Support (ECLS) Circuits

Abstract: Though much has been surveyed and written about the equipment aspects of extracorporeal life support (ECLS) in the past 10 years, there is value in reviewing the use and nonuse of multiple safety devices and techniques. Minimally equipped ECLS circuits for adult and pediatric bridge to decision during cardiac and respiratory failure are rapidly gaining popularity to maintain simplicity and portability. ECLS circuits employed for long-term therapy are outfitted differently and should include more safety devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…More recently, however, thanks to improvements in technology, safety profile and manageability of extracorporeal life support strategies [ 16 , 17 ], ECMO has been reintroduced in some centers as an option for patients with severe respiratory failure awaiting lung transplant [ 4 , 10 , 13 , 18 – 22 ]. The number of lung transplant candidates who could benefit from ECMO is now significantly larger [ 13 , 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, thanks to improvements in technology, safety profile and manageability of extracorporeal life support strategies [ 16 , 17 ], ECMO has been reintroduced in some centers as an option for patients with severe respiratory failure awaiting lung transplant [ 4 , 10 , 13 , 18 – 22 ]. The number of lung transplant candidates who could benefit from ECMO is now significantly larger [ 13 , 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its role extends even further as an adjunct to cardiopulmonary resuscitation (CPR) 4 , as well as high risk percutaneous cardiac interventions 5 . Improvements in equipment, patient selection and a better understanding of extracorporeal circuit technology have resulted in some centres reporting significantly improved outcomes [6][7][8] . The Conventional Ventilation or ECMO for Severe Adult Respiratory Failure (CESAR) trial 9 , and the Australian and New Zealand Intensive Care Society ECMO investigator study into Influenza A (H1N1) 10 , have demonstrated its usefulness in the advanced management of respiratory failure unresponsive to maximal conventional therapy [11][12][13][14] .…”
mentioning
confidence: 99%
“…Membrane oxygenators and pumps are the main elements of the ECMO system, and outcomes depend on them. Impressive technical progress has been made in pumps, oxygenators, and coatings for artificial surfaces, leading to greater biocompatibility and a lower rate of procedure‐related complications (3,4). Oxygenators have primarily used the silicone rubber membrane, then the microporous polypropylene hollow‐fiber membrane, and recently the polymethylpentene (PMP) membrane.…”
mentioning
confidence: 99%